PHP code smells in web apps - Rio, Américo (2023)
Rio, A., & Abreu, F. B. E. (2023). PHP code smells in web apps: Evolution, survival and anomalies. Journal of Systems and Software, 200, 1-23. [111644]. https://doi.org/10.1016/j.jss.2023.111644 ---%ABS2%